Nanomaterials in Wound Healing: Mechanisms, Applications, and Future Prospects - Rani, Kavita; Singh, Gurvirender; Narwal, Smita; Chopra, Bhawna; Dhingra, Ashwani K. (Current Nanomedicine, 2025)
BackgroundPoor wound healing poses a significant global health challenge, leading to increased mortality rates and considerable healthcare expenses. Nanotechnology has emerged as a promising approach to address the complexities associated with wound healing, offering potential solutions to enhance the wound microenvironment and promote efficient tissue repair.AimThis review aims to comprehensively summarize recent advancements in the application of nanomaterials for wound healing, with a focus on their mechanisms of action. The review also explores the prospects and challenges of using nanomaterials in wound dressings, specifically in the context of antimicrobial, anti-inflammatory, and angiogenic effects.ResultsThe integration of nanomaterials in wound healing has demonstrated significant progress in addressing key challenges, such as providing a suitable environment for cell migration, controlling microbial infections, and managing inflammation. Nanomaterials have been found to stimulate cellular and molecular processes, promoting hemostasis, immune regulation, and tissue proliferation, thereby accelerating wound closure and tissue regeneration.ConclusionNanotechnology-based wound healing has shown great promise in revolutionizing wound care. Nanomaterials offer unique physicochemical and biological properties that can be harnessed to develop advanced wound dressings capable of sustained therapeutic agent delivery and targeted bacterial detection and treatment. Despite these promising advancements, challenges such as reproducibility, stability, toxicity, and histocompatibility must be addressed to ensure successful translation from laboratory research to clinical applications. Further research is required to better understand the in-vivo behaviour of nanomaterial-based wound dressings and to explore innovative approaches, such as intelligent wound dressings that detect and treat infections synergistically, to enhance wound healing outcomes. Overall, nanomaterials hold tremendous potential for future wound healing strategies, paving the way for improved patient outcomes and reduced healthcare burdens.
Keywords: Nanomaterial